Comparative Evaluation Study of Rk39 Dipstick and On-Site Leishmaniasis Testing for the Retrospective Diagnosis of Visceral Leishmaniasis in Misan Governorate, Iraq - Abul-Doanej, Hasan Azaati Ibadi (American Journal of Biology and Natural Sciences, 2025)
This retrospective study evaluated diagnostic accuracy of the rK39 strip test and the On-Site leishmaniasis technique for the identification of visceral leishmaniasis (VL) in Misan Governorate, Iraq. VL, caused by various Leishmania strains, used to require invasive diagnostic procedures. This study aimed to determine the impact of non-invasive serological testing procedures, specifically the IgG/IgM combined in situ leishmaniasis test (ISLT), introduced in Iraq in 2017, as well as the eK39 dipstick assay, known for its parameters rate (sensitivity and specificity). Human serum samples were collected and tested using both methods. The results indicate a correlation between the two tests, suggesting their suitability to aid in diagnosis in the examined samples. The two diagnostic tools did not show any statistically significant differences (P>0.05). These findings contribute to our understanding of visceral leishmaniasis diagnostic methods and their applicability in Iraq, indicating that both the on-site IgG/IgM visceral leishmaniasis test and the rK39 strip test provide reliable, non-invasive alternatives for diagnosing this disease.